FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS QUALITY PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Tony Sudirgo (Universitas Bunda Mulia, 2021)
The purpose of this study is to analyze board diversity, leverage and profitability of earnings quality in manufacturing companies listed in Indonesia Stock Exchange, especially from period 2016-2018 as population. Purpose sampling as a sampling method with a total of 105 data in the form of financial statements from www.idx.co.id. The analytical method used is panel data regression analysis with the E-Views 9.0 program. The results of the study indicate that only profitability affects earnings quality while Board diversity and leverage don’t affect earnings quality.